2022
DOI: 10.1186/s10033-022-00721-4
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Validation Study on Ferrofluid Evaporation

Abstract: The current research on the evaporation of ferrofluids mainly focuses on the characterization of ultra-low vapor pressure ferrofluids in vacuum and the theoretical analysis of the evaporation process. Few studies have focused on the experimental validation of the proposed evaporation rate equations and on the comparison of the differences in ferrofluid evaporation. In this study, based on the Bolotov’s model, an evaporation rate equation is deduced from the experimental model. The experimental study included a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…This paper uses kerosene-based magnetic fluid to conduct evaporation experiments, where the size of the magnetic particles is 10 nm. (Yu et al, 2022). The kerosene-based magnetic fluid was injected into four identical flat-bottomed test tubes in equal amounts, and an evaporation experiment in the same environment was carried out in a high and low temperature test chamber as shown in Figure 7.…”
Section: Magnetic Fluid Evaporation Experimentsmentioning
confidence: 99%
“…This paper uses kerosene-based magnetic fluid to conduct evaporation experiments, where the size of the magnetic particles is 10 nm. (Yu et al, 2022). The kerosene-based magnetic fluid was injected into four identical flat-bottomed test tubes in equal amounts, and an evaporation experiment in the same environment was carried out in a high and low temperature test chamber as shown in Figure 7.…”
Section: Magnetic Fluid Evaporation Experimentsmentioning
confidence: 99%
“…(2015) found that electrostatic spraying increased droplet coverage and liquid deposition in the canopy, middle, and lower layers of the target. Yu et al. (2005) realized that the droplet spectrum of electrostatic spraying was narrower and the effective deposition of pesticides increased significantly.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, a flexible DTM uses the elastic deformation of the material to realize the transmission of motion [22]. It has the characteristics of fewer parts, no gaps between the moving parts, and no mutual wear; therefore, it is more widely used [23]. Bu et al [17] designed a triangular amplified flexible transmission dispenser, and its transmission ratio model was established according to the geometric relationship of the structure.…”
Section: Introductionmentioning
confidence: 99%